Sound absorption and impedance study of lignocellulosic fibre based composites for acoustical applications - Elammaran, Jayamani (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study investigates five types of lignocellulosic fibres reinforced polymer matrix composites to be applied for the acoustical material component. In this work, three thermoplastic binders were used, which include polypropylene (PP), poly lactic acid (PLA) and zein. The two thermoset binders used were epoxy and unsaturated polyester. The five lignocellulosic fibres include rice straw, luffa, sisal, oil palm empty fruit bunch, and betel nut. The weight percentage of fibres used ranged from 5 wt.% to 30 wt.%. Hot compression moulding was used in the preparation of specimens for thermoplastic composites. The cold compression process was used in preparation of specimen for thermoset binders. Chemical and physical surface modifications were carried out on natural fibres to enhance the interfacial adhesion between the fibres and the matrix. In this work, sodium hydroxide and heat treatment were used to modify the hydrophilic properties of natural fibres. The effects of this surface modification on the sound absorption, mechanical, and dielectric properties of the composites were measured. Two units of two-microphone transfer function impedance tube devices were fabricated in the laboratory, according to the American Society for Testing Materials, ASTM E1050-12. The first unit was used to measure sound absorption coefficients in the frequency range of 500 Hz to 2000 Hz. The second unit was used to measure the frequency ranging from of 2000 Hz to 6000 Hz. Later, the results from both units were combined to obtain the sound absorption coefficient (α) for the frequency range between 500 Hz to 6000 Hz. Prior to the measurements, a relative calibration of microphone pairs was performed according to ASTM E1050-12 standards. The structural and thermal decomposition of the fibres and their reinforced composites before and after surface treatments were investigated through fibre morphology analysis (scanning electron microscope (SEM)), Fourier transform infrared spectroscopy (FTIR) analysis, and thermo-gravimetric analysis (TGA). Generally for all the composites tested, the composites made of treated fibre had higher sound absorption coefficients than the untreated fibre composites. Increase in fibre content generally leads to higher sound absorption coefficients, with exceptions at certain frequencies. A slight difference in sound absorption coefficients was observed among the five types of composites tested. In these tested composites, the sound absorption coefficients of rice straw/PP composites were found to be the highest. Generally for all the composites tested, the dielectric constant, dissipation factor and loss factor of composites increased with fibre content for the entire range of frequencies. This increase was high at low frequencies, low at medium frequencies, and very low at high frequencies. The dielectric constant, decreased with frequency due to the decreased interfacial and orientation polarization at higher frequencies. The fibre surface modifications by alkaline and heat treatments improves the fibre matrix adhesion, which in turn improves the mechanical properties of composites until the optimum wt.% of fibre. These results were confirmed through SEM and FTIR analysis. After surface modifications, the SEM characterisation showed that the surface modifications changed the morphology of fibres, resulting in the increase of sound absorption coefficients of composites. For all the fibres tested, FTIR spectra confirmed that the shifts in the functional groups that occurred were a result of surface treatments. These shifts show the effectiveness of treatments on the fibres. The TGA thermographs for all the five composites tested have been observed with a slight difference in decomposition temperatures. Thermo-gravimetric analysis revealed that moisture absorbed by the natural fibres was primarily due to the presence of hemicellulose. Hemicellulose also exhibited lower thermal stability compared to cellulose and lignin constituents. Thermal analysis revealed that, the presence of hemicellulose constituents in the untreated fibres had lower thermal stability. Cellulose showed higher decomposition temperatures compared to lignin. Lignin decomposed over a broad temperature range. Treated fibre composites showed higher thermal decomposition temperatures compared to the thermal decomposition temperatures of the untreated fibre composites.